ANGELIKA NEUWIRTH: KAJIAN INTERTEKSTUALITAS DALAM QS. AL-RAá¸¤MÄ€N DAN MAZMUR 136 - Rahman, Zayad Abd. (IAIN Kediri, 2015)
Angelika Neuwirth is a typical Western scientist who contributed to the reviews of the QurÃ¢â‚¬â„¢an through a literaryÃ‚Â approach. Neuwirth builds her analysis on letters as a whole. In a further development, Neuwirth suggestedÃ‚Â the use of letters not only in literary approaches, but also in historical ones. For her, a letter is a small unit thatÃ‚Â stores a communication process from birth; it is also an integral unit that the editor guarantees as a literaryÃ‚Â text. She understands the QurÃ¢â‚¬â„¢an as a living scripture that reacts to other traditions during its emergence.Ã‚Â With the study of intertextuality, the BibleÃ¢â‚¬â„¢s influence on the QurÃ¢â‚¬â„¢an is not considered a plagiarism, rather aÃ‚Â uniqueness and effectiveness of the QurÃ¢â‚¬â„¢anic messages.Keywords: Studi al-QurÃ¢â‚¬â„¢an, Intertekstualitas, Literatur.